Managing multiple masculinities in donor insemination: doctors configuring infertile men and sperm donors in Taiwan - Wu, Chia‐Ling (Sociology of health & illness, 2011)
This article investigates how doctors configured infertile men and sperm donors in the development of donor insemination (DI) in Taiwan. In the initial stage (1950s–1970s) doctors adjusted clinical procedures to repair the deformed gender identities of infertile men. To expand DI in the late 1970s and early 1980s, doctors stressed the positive eugenics of DI by spotlighting the high intelligence of donors, playing down biological patrilineage and re‐emphasising the contribution of men of higher rank in society. In the mid‐1980s, when donors came to be seen as potential carriers of fatal diseases like acquired immune deficiency syndrome, doctors managed to associate risky donors with socially stigmatised men, and therefore perpetuate the conventional hierarchy of masculinities. As the intracytoplasmic sperm injection emerged in the early 1990s doctors quickly presented infertile men as universally longing for biological fatherhood and hence devalued DI in an attempt to augment paternal masculinity. These diverse configuration activities come together to create a socio‐technical network of DI that most of the time perpetuates the reigning gender order, rather than destabilising it. I argue the importance of incorporating various types of participants in analysis to understand the changing dynamics of multiple masculinities along with the development of DI.